The exemplary adaptation to imperial order: the Baitokin family's service, life, and nobility (Journal of history-rus, 2023)
Abstract. The 19th-century social changes in the Kazakh steppe resulted from the emergence of new social classes within Kazakh society, including nobles, honored citizens, imperial officials, and intellectuals. Although privileged estates were traditionally associated with sultans, there were influential noble families from non-aristocratic backgrounds in the Kazakh community. These families earned their noble status through personal merit and loyalty to the imperial authority, creating a path to the upper class facilitated by the Russian administration for non-elitist groups in Kazakh society. The Baitokin family stands out as an intriguing illustration of Kazakh nobility, showcasing a distinctive combination of dedicated service as imperial officials and local innovators. This article discusses the Baitokin family, as Kazakh noble lineage, and their remarkable ability to adapt to the imperial political and social order. It also explores their influential role in propagating imperial rule throughout the Kazakh steppe and contributing to the socio-economic development of the people they governed. The main argument put forward is that the Baitokins played a significant part in the institutionalization process of the empire in the Steppe, while simultaneously promoting the adoption of a sedentary way of life among the Middle Horde Kazakh society.